PELATIHAN STRATEGI PENENTUAN TARGET PASAR DAN BRANDING PRODUK DIGITAL BAGI DINKOMINFO PURBALINGGA - Rofi Puspitaningtias; Lita Ningrum Afriani; Libran Filani; Endah Ika Hastuti (Abdi Jurnal Publikasi, 2026)
Digital transformation requires local governments to deliver public information effectively, precisely, and with a strong identity. The Purbalingga Regency Communications and Informatics Office (Dinkominfo) plays a strategic role in managing public communications through various digital products. However, the challenges faced include suboptimal target market (audience) determination and branding strategies for government digital products, resulting in low information delivery effectiveness and public engagement. This Community Service (PKM) activity aims to improve the understanding and capabilities of Dinkominfo officials in determining target audiences and building branding for local government digital products. The method used was community education with a participatory approach, implemented through interactive lectures, discussions, and simple simulations based on real-world problems. The results of the activity showed an increase in participants' understanding of the concept of audience segmentation and the basic principles of digital product branding, both quantitatively and qualitatively. Participants also demonstrated active participation and were able to formulate initial strategies contextualized to their work conditions. This activity demonstrates the effectiveness of community education with a participatory approach in increasing the capacity of local government officials. This PKM activity is expected to support more strategic public communications management and strengthen the image of local government in the digital era.